Klebsiella pneumoniae detection by a light-controlled one-pot RPA-CRISPR/Cas12a method - Pan, Lele; Wei, Lijian; Luo, Shihua; Ren, Baoyan; Li, Miao; Liang, Lina; Li, Xuebin; Wei, Guijiang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundKlebsiella pneumoniae (KP) is a significant pathogenic bacterium responsible for severe infections in hospitals. However, existing traditional detection techniques, such as culture and PCR, are relatively inefficient. Therefore, this study aims to establish a rapid and convenient method for detecting KP.MethodsThis study developed a single-tube detection method combining recombinant polymerase amplification (RPA) and light-controlled CRISPR/Cas12a. RPA primers were designed and screened for the rcsA gene of KP to effectively amplify the target. A light-controlled CRISPR/Cas12a system was created using crRNA modified with a photocleavable group (NPOM). The two systems were integrated into a single tube. Following RPA amplification, UV light-controlled release of crRNA inhibition activates CRISPR-mediated target recognition and Cas12a trans-cleavage, detecting fluorescent signals (FD) in conjunction with UV analysis.ResultsThe light-controlled RPA-CRISPR/Cas12a detection platform developed in this study uses a 15 μL reaction system. By optimizing key parameters such as RPA amplification time (20 min), primer concentration (400 nM), UV light activation time (30 s), and crRNA/Cas12a concentration (300 nM), the platform achieves optimal detection efficiency. The platform has a fluorescence detection limit of 4.072×102 copies/reaction and can specifically identify KP in seven common clinical strains. Clinical sample validation demonstrated that the method yields results fully consistent with PCR detection (30/30 agreement rate of 100%), showcasing excellent detection performance and clinical application potential.ConclusionWe have successfully developed a light-controlled RPA-CRISPR/Cas12a detection system capable of rapidly and highly sensitively detecting KP. This system demonstrates significant advantages in terms of detection speed (completed in as little as 50 minutes), sensitivity (as low as 4.072×102 copies/reaction), and ease of use, providing an efficient and reliable solution for clinical pathogen detection.